Детермінація умисних посягань на життя людини в Україні - Кушніренко, Р. О.; Kushnirenko, R. O. (Юридична наука. - 2020. - № 2, т. 2. - С. 56-67, 2020)
У статті досліджено детермінуючі ознаки умисних посягань на життя людини в Україні шляхом аналізу статистичної інформації, яка відображає стан цього виду злочинності, його динаміку, географію. Встановлено збільшення питомої ваги окремих видів умисних вбивств, які вчинюються при обтяжуючих обставинах, загальний масив злочинних посягань на життя формується переважним чином за рахунок «звичайних» вбивств (побутових, ситуативних тощо).

The article examines the trends of criminal deaths in Ukraine during 2001‒2014 by analyzing statistical information that reflects the state of this type of crime, its dynamics, and geography. An increase in the specific weight of certain types of intentional murders, which are committed under aggravating circumstances, has been established, the overall array of criminal assaults on life is predominantly formed at the expense of "ordinary" murders (domestic, situational, etc.). If in the 90s the potential murderers were persons serving sentences for relevant crimes, members of the OG and ZO, persons who were on the register, and the victims were entrepreneurs, wealthy citizens, persons who had power or a sphere of influence, then nowadays, a potential murderer is any member (father, mother, one of the children) of every tenth, usually uncharitable, family. The victim is the same family members, neighbors, acquaintances, etc. It is clear that in such a situation, law enforcement officers are simply not able to effectively carry out preventive activities, take measures to prevent intentional murders and attempts on them, because there are too many people to prevent them (including victims with provocative behavior). Despite the decrease in the total number of intentional homicides over the past decades, changes in the structure of intentional homicides, and a decrease in the total number of homicides committed under certain aggravating circumstances, this area currently requires priority attention from law enforcement agencies, the state, the development of effective measures to prevent these dangerous encroachments, the creation of and implementation of effective measures to protect life and health of citizens.

Исследованы детерминирующие признаки умышленных посягательств на жизнь человека в Украине путем анализа статистической информации, отражающей состояние этого вида преступности, его динамику, географию. Установлено увеличение удельного веса отдельных видов умышленных убийств, совершаемых при отягчающих обстоятельствах, общий массив преступных посягательств на жизнь формируется преимущественно за счет «обычных» убийств (бытовых, ситуативных и т.п.).
Keywords: життя людини; умисні посягання на життя; детермінанти злочинності; кримінальні смерті; убивство; запобігання злочинності; злочинність; human life; deliberate encroachments on life; determinants of crime; criminal deaths; murders; crime prevention; crime; жизнь человека; умышленные посягательства на жизнь; детерминанты преступности; криминальные смерти; убийство; предотвращение преступности; преступность